Pigmented Bowen's disease - Amanda Nascimento Cavalleiro de Macedo Mota; Juan Piñeiro-Maceira; Maria de Fatima Guimarães Scotelaro Alves; Mónica Jidid Mateus Tarazona (Sociedade Brasileira de Dermatologia, 2014)
Pigmented Bowen's disease is rare, though more prevalent in men. It presents as a well-delineated plaque in areas unexposed to sun. There are reports of association with seborrheic keratosis, solar lentigo or exuberant pigmentation of genital and intertriginous regions. A specific dermoscopy finding is the presence of brown or gray dots in regular arrangement and coiled or dotted vessels. Thus, we aim to raise awareness of the diagnosis of pigmented Bowen's disease in pigmented lesions.